Seismic monitoring in the Gugla rock glacier (Switzerland): ambient noise correlation, microseismicity and modeling - Guillemot, Antoine; Helmstetter, Agnes; Larose, Éric; Baillet, Laurent; Garambois, Stephane; Mayoraz, Raphaël; Delaloye, Reynald (Geophysical Journal International, 2020)
International audience A network of seismometers has been installed on the Gugla rock glacier since October 2015 to estimate seismic velocity changes and detect micro-seismicity. These two processes are related to mechanical and structural variations occurring within the rock glacier. Seismic monitoring thus allows a better understanding of the dynamics of rock glaciers throughout the year. We observed seasonal variations in seismic wave velocity and micro-seismic activity over the three years of the study. In the first part of our analysis, we used ambient noise correlations to compute daily changes of surface wave velocity. In winter, seismic wave velocities were higher, probably due to refreezing of the active permafrost layer and cooling of the uppermost permafrost layers, leading to increased overall rigidity of the medium. This assumption was verified using a seismic model of wave propagation that estimates the depth of P-and S-wave velocity changes from 0 down to 10 m. During melting periods, both a sudden velocity decrease and a decorrelation of the seismic responses were observed. These effects can probably be explained by the increased water content of the active layer. In the second part of our study, we focused on detecting micro-seismic signals generated in the vicinity of the rock glacier. This seismic activity (micro-quakes and rockfalls) also exhibits seasonal variations, with a maximum in spring and summer, which correlate with acceleration of the rock glacier's displacement rate. In addition, we observed short bursts of micro-seismicity, both during snowfall and during rapid melting periods. All these observations could be included in systems monitoring permafrost and slope destabilization, to complement existing records.